Los pictogramas y el lenguaje oral en los niños del nivel inicial II de la Escuela de Educación Básica 18 de Noviembre de la ciudad de Loja, periodo 2021- 2022. - Guarderas Cabrera, Nancy Mirvana (2022)
Oral language is the ability to communicate verbally and linguistically through conversation and is learned since childhood, it is developed from codes or signs in order to organize joint activities of a group or groups of individuals to establish an interaction. The general objective of the research is to determine how pictograms improve oral language in children of the initial level II of the Escuela de Educación Básica 18 de Noviembre of the city of Loja Period 2022; a quasi-experimental research of mixed approach was conducted with the following methods: inductive, deductive, analytical and synthetic with the help of the technique: the interview and finally with the help of the instrument: PLON-R Test (Oral Language Test Navarra - Revised) developed by Aguinaga et. al (2004). The study population consisted of 22 children and one teacher, taking into account the data from the pre-test, it was evident that at the beginning when the pre-test was applied, the children did not know how to answer questions such as what is their name, they could not repeat phonemes or short phrases, it was very difficult for them to decipher an image, and post-test the improvement obtained after the application of the alternative proposal based on an activity guide can be noted, The research was not 100% effective due to different factors, but taking into account the development of oral language allowed the children to make a satisfactory school learning, on which all subsequent knowledge for the understanding and acquisition of a fluent oral language is based; In other words, their educational development throughout their school years depends on it, and it will serve as a tool to communicate and be able to live in society. Pictograms are an important ludic tool for the improvement of oral language. Key words: Oral language, verbal communication, pictograms, activities.